RNA interferência como alternativa para o controle de helicoverpa armigera mediante silenciamento gênico - Ceccon, Cássia Canzi (2016)
Helicoverpa armigera is a pest insect of several economically important crops. Research groups have studied RNA interference (RNAi) to knock down expression of vital genes within target pests. Successful reduction of the expression of these genes can lead to mortality and affect the insect development. The objective of this work was to evaluate the ability of orally introduced double strand RNA (dsRNA) matching the H. armigera larvae rieske gene to induce an RNAi response and to cause mortality. The rieske gene encodes a mitochondrial protein involved in the electron transport and energy production. We hypothesize that dsRNA will enter the gut epithelial cells and induce an RNAi response that reduces rieske gene expression, and consequently, reduce energy production. This should reduce the cells ability to perform digestive functions resulting in larvae mortality. The experiments were performed in the Plant Biotechnology and Entomology Laboratories of the University of Passo Fundo. Initially, a profile of developmental changes in the rieske transcript was developed for dissected digestive tracts and whole insects and appropriated reference genes were identified for use with RT-qPCR. Second, the dsRNA dose most effective at inducing larvae mortality was determined. Subsequently, the occurrence of gene silencing and its relationship with larval mortality and development was evaluated. The RT-qPCR reference genes found to be the most stable for normalization of rieske gene expression were elongation factor 1-α (ef1-α) and glyceraldehyde 3-phosphate dehydrogenase (GAPDH). The rieske dsRNA dose of 0,3 µg.cm-2was most effective at inducing larvae mortality, reducing weight gain and inhibiting leaf consumption. Delivering 0.3 µg.cm-2of dsRNA rieske every two days to soybean leaf discs caused a reduction in the rieske gene transcripts and increased Helicoverpa armigera larval mortality. But when the feeding of leaf discs treated with dsRNA was interrupted with untreated leaf disks similar effects were not observed. These results indicate that the RNAi mediated gene silencing of rieske has the potential to be used as H. armigera control, however for increased effectiveness, the delivery of the dsRNA must be continuous.